Analyzing Distinct Attributes of Shifts in Customer Behavior within the Banking Services Sector (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
Consumer behavior in the banking industry has seen substantial changes due to technological improvements, changing cultural values, and developing customer expectations. This study seeks a thorough understanding of the theoretical and methodological principles that form the basis of these developments. This paper analyzes many essential theoretical frameworks, including the theory of planned behavior, technology acceptance model, and customer engagement theory, via a literature analysis. These frameworks provide valuable insights into the elements that influence consumer behavior in the banking industry. Furthermore, it examines various methodological strategies such as surveys, interviews, and data analytics used to explore and evaluate trends in consumer behavior. This study offers significant insights for academics and business by combining current research. It assists in developing strategies that successfully respond to the changing dynamics of customer behavior in the financial services market.